An Islamic perspective on multicultural counselling: a Malaysian experience of Triad Training Model (TTM) - Hassan, Siti Aishah; Peh, Kai Shuen (IDOSI Publications, 2014)
This paper confers an Islamic perspective of multicultural counselling. An anecdote from the authors’ Triad Training Model (TTM) experience of the supervisor - intern - client of Islam-Buddhism-Christian cross-cultural counselling is provided. The paper then enumerates the importance of ethnic racial identity in multicultural counselling. Accordingly, the supervisor’s multicultural competencies are discussed and the shades of spirituality according to Islam, Buddhism and Christianity are provided. Finally, this paper concludes with the resistance towards multicultural counselling and a summary ends the paper.